TECTONICS OF ICY SATELLITES DRIVEN BY MELTING AND CRYSTALLIZATION OF WATER BODIES INSIDE THEIR ICE SHELLS - Johnston, Stephanie Ann (2015)
Enceladus and Europa are icy satellites that currently support bodies of liquid water in the outer solar system Additionally, they show signs of being geologically active. Developing numerical models informed by observations of these icy satellites allows for the development of additional constraints and an improved understanding of the tectonics and evolution of icy satellites. The formation mechanisms for both chaos and ridges on Europa are thought to involve water as albedo changes observed in association with them imply the deposition of salt-rich water near these features. Ridges are the most ubiquitous feature on Europa and are described as central troughs flanked by two raised edifices, range in height from tens to hundreds of meters. Europan ridges can extend hundreds of km continuously along strike but are only about 2 km across. A model of a crystallizing dike–like water intrusion is able to match the overall morphology of ridges, and is consistent the long continuous strike. However, the intrusion of a large volume of water is required to match the most common heights of the ridges. Chaos on Europa is defined as a large area of disrupted ice that contain blocks of pre-existing material separated by a hummocky matrix. A proposed mechanism for the formation of Chaos is that a region of heterogeneous ice within the shell is melted and then recrystallizes. Comparing the model results with the geology of Thera Macula, a region where it has been proposed that Chaos is currently forming, suggests that additional processes may be needed to fully understand the development of Chaos. Water-rich plumes erupt from the south pole of Enceladus, suggesting the presence of a pressurized water reservoir. If a pressurized sea is located beneath the south polar terrain, its geometry and size in the ice shell would contribute to the stress state in the ice shell. The geometry and location of such an ocean, as well as the boundary conditions and thickness of an ice shell have important implications for the faulting and ...